A study on exploring the hiring preferences of selected school libraries with reference to gender - Cantal, Rowell G.; Obille, Kathleen Lourdes (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Librarianship has traditionally been seen as women's work, along with nursing and teaching school. In our society where gender became diverse, openness, readiness and acceptance of the society is in question most especially in the profession industry.
The study focused on the hiring preferences in reference to gender of the five schools which participated in the study. The researcher assessed if the school libraries have preferential treatment based on the gender of the applicants and whether the school libraries prefer a certain gender for filling a particular position in the library. In addition, the study attempted to know if the participating schools accept applicants from a diverse gender group or the LGBT community to fill in key positions.
The data gathered from the interviewed revealed that the five different catholic schools; (a) give importance to the educational attainment of the applicant, (b) majority (87.5%) of the school personnel who are involve in hiring don't lean towards any specific gender when filling in a particular position in the library, (c) the five schools do not have policies involving gender preferences when hiring school librarians (d) the five schools do not have preferential treatment based on their gender when applying for a library position and (e) the five schools are open in hiring applicants of diverse gender types or member of the LGBT community for the librarian position.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Employee selection -- Philippines; School libraries -- Philippines